Cost‐effectiveness analysis of postpolypectomy colonoscopy surveillance using Japanese data. Issue 1 (6th September 2018) - Sekiguchi, Masau; Igarashi, Ataru; Sakamoto, Taku; Saito, Yutaka; Esaki, Minoru; Matsuda, Takahisa
Abstract : Objective: Recommendations vary on postpolypectomy surveillance, and no consensus has been reached even regarding the necessity of risk stratification based on polyp characteristics for surveillance. We examined an optimal postpolypectomy surveillance program by performing a cost‐effectiveness analysis. Methods: We performed a Markov model analysis using parameters based on Japanese data and evaluated four postpolypectomy surveillance programs with respect to their effectiveness in terms of quality‐adjusted life‐years (QALYs), cost‐effectiveness and required number of colonoscopies. Two were non‐risk‐stratified programs with 1‐year (program 1) and 3‐year (program 2) postpolypectomy surveillance colonoscopy, and the other two were risk‐stratified programs. In program 3, surveillance colonoscopy was performed 3, 10 and 10 years after resection of advanced adenomas, low‐risk adenomatous polyps, and no polyps, respectively. In program 4, those intervals were shortened to 1, 3 and 5 years, respectively. Results: Risk‐stratified programs (3 and 4) yielded higher QALYs with lower costs than non‐risk‐stratified programs (1 and 2). Program 4 yielded higher QALYs (23.046) and lower required cost (107, 717 JPY) than program 3. The required number of colonoscopies for program 4 was 1.2, 1.5 and 1.6 times that for programs 1, 2 and 3, respectively. A probabilistic sensitivity analysis showed that the probability of program 4 being chosen as the most cost‐effective was highest. Conclusions: After polypectomy, risk‐stratified colonoscopy surveillance based on the polyp characteristics should be considered. A risk‐stratified program with relatively short examination intervals could be effective and cost‐effective in Japan, although further investigation and consideration of colonoscopy capacity are required.